Wood Damages and Improvement in Rural Mosques: Ordu Mosque - Şengül Yalçınkaya (Journal of Architectural Sciences and Applications, 2023)
This study discusses the damage to wooden materials, which is among the most common problems in the protection of wooden mosques and conveys this issue through examples of mosques in the region. In the case of Ordu mosque, the problems and interventions in wooden materials were analyzed. The condition of the wooden material in the building and the protection approach was examined through the protection and art report of the mosque, the relief and restoration drawings, and photographs. Problems have been identified in wood due to regional conditions, time, transportation, and lack of maintenance and repair. The approach of conserving the original parts was adopted, and the material was renewed at the point where there was deterioration, loss or decrease in strength. It has been revealed that the research in the field should be increased and new strategies for protection should be developed by evaluating the data holistically.